Quality Deterioration of Boiled Salted Carp Fish (Cyprinus carprio), Processed using Different Cooking Methods, During Chilling Storage - Dwi Suryaningrum, Theresia; Syamdidi, Syamdidi (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2013)
Study on quality changes of boiled salted Carp  fish, processed using different cooking  methods during chilling storage has been conducted. The  study was  intended to obtain an information on  the effect of cooking method on  the shelf-life of boiled salted carp fish (Cyprinus carpio) at chilling temperatures. Fish was soaked in a 0.2% of alum solution and then marinated in condiment solution for 30 minutes. Fish were cooked for 4 h by two different methods i.e steaming and boiling,  at 98-100 oC,  and then dried  in the oven at 80-90 oC for 1 hour. Boiled salted fish  then were  stored at chilling room (2-4 oC)  and observed every 3 days for 15 days.  The quality of boiled salted  fish were analyzed  i.e proximate at the beginning and the end of storage, while moisture content, pH, TVB, total plate count, mold and sensory test were conducted  during chilling storage. The results showed that steamed boiled salted  carp  fish had higher protein content, pH and also have better product which was preferable by the panelists. Based on this result  steaming method   was recomended to be used as processing method for production  of boiled salted  carp fish from fresh water.  Sensory test found that panelists preferred steamed  product which had a good appearance, odor, taste  and texture.  However steamed product had faster increase of  moisture content, TVB, and number of  bacteria as well as the decrease of pH value and odor causing faster deterioration of product compared to boiling method. Based on microbiological  tests, the boiled salted carp fish cooked by steaming  methods  were  safe to be consumed before 6 days  and the boiling method before 9 days, since storage exceed that periods resulted in  number  of bacteria already reached the maximum number allowed  and became not suitable for human consumption.